Low speech rate but high gesture rate during conversational interaction in people with Cornelia de Lange syndrome. Issue 6 (10th March 2021) - Pearson, E.; Nielsen, E.; Kita, S.; Groves, L.; Nelson, L.; Moss, J.; Oliver, C.
Abstract: Background: Cornelia de Lange syndrsome (CdLS) is a rare genetic syndrome with notable impaired expressive communication characterised by reduced spoken language. We examined gesture use to refine the description of expressive communication impairments in CdLS. Methods: During conversations, we compared gesture use in people with CdLS to peers with Down syndrome (DS) matched for receptive language and adaptive ability, and typically developing (TD) individuals of similar chronological age. Results: As anticipated the DS and CdLS groups used fewer words during conversation than TD peers ( P < .001). However, the CdLS group used twice the number of gestures per 100 words compared with the DS and TD groups ( P = .003). Conclusions: Individuals with CdLS have a significantly higher gesture rate than expected given their level of intellectual disability and chronological age. This result indicates the cause of reduced use of spoken language does not extend to all forms of expressive communication.